Unusual form of relationship between parasitic nematodes of the genus Philonema (Philonemidae) and salmonids - V. V. Pospekhov; V. P. Nikishin (Российский паразитологический журнал, 2020)
The purpose of the research is studying the relationship between nematodes of the genus Philonema (Philonemidae) and salmonids at the organismic level and justification for their interpretation as a peculiar form of encapsulation.Materials and methods. We studied the sockeye salmon, as well as the freshwater white-spotted char and Dolly Varden trout from lakes Kisi and Chistoye (basin of the Ola River, Taui Bay, Sea of Okhotsk). 7 males for breeding sockeye salmon, 39 freshwater white-spotted chars and 16 Dolly Varden trouts were dissected for infection by Philonema. We used well-known generally accepted techniques in the parasitological studies. The nematodes were preserved in 70 % ethanol and clarified in glycerol.Results and discussion. Phylonema causes pathological processes of various intensity in the body cavity of salmonids. As a rule, this is the adhesion of fish’s internal organs and the formation of a thick layer of connective tissue that surrounds the host's organs from outside and forms a kind of a "cocoon". Our studies combined with literature data allow us to consider the formation of a "cocoon" as a peculiar form of encapsulation and an adaptation that minimizes mutual negative impact of the parasite and the host on each other. Further research should determine how widespread this form of encapsulation is in nature, and it is also necessary to study the mechanism of the "cocoon" formation.